2006
DOI: 10.1111/j.1365-2966.2006.11079.x
|View full text |Cite
|
Sign up to set email alerts
|

The clustering of narrow-line AGN in the local Universe

Abstract: We have analyzed the clustering of ~ 90,000 narrow-line AGN drawn from the Data Release 4 (DR4) of the SDSS. We compute the cross-correlation between AGN and a reference sample of galaxies, and compare this to results for control samples of inactive galaxies matched simultaneously in redshift,stellar mass,concentration, velocity dispersion and the 4000A break strength. We also compare near-neighbour counts around AGN and around the control galaxies. On scales larger than a few Mpc, AGN have almost the same clu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
139
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(155 citation statements)
references
References 68 publications
15
139
1
Order By: Relevance
“…In fact, they are not expected to yield an appreciable enhancement in the clustering of AGN hosts (see Taniguchi 1999; see also Stewart 2009;Lotz et al 2011). Thus the controversial observational results concerning the clustering of the AGN hostssee Li et al (2006), Pierce et al (2007), Darg et al (2010) for negative evidence, and Alonso et al (2007), Woods & Geller (2007), Rogers et al (2009), Koss (2010, and Ellison (2011) for an enhanced fraction of close pairs of AGN hosts compared to control samples -can hardly provide a definite clue to the minor merging/fly-by scenario (also because of the dependence of the results on the clustering scale). A support for the interactionbased picture can be found in the bluer colours of galaxies close to AGN hosts (see Shirasaki et al 2011;Kollatschny et al 2012), and in the observations of specific individual cases (see, e.g., Gonzalez Delgado et al 2002;Anderson et al 2013 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, they are not expected to yield an appreciable enhancement in the clustering of AGN hosts (see Taniguchi 1999; see also Stewart 2009;Lotz et al 2011). Thus the controversial observational results concerning the clustering of the AGN hostssee Li et al (2006), Pierce et al (2007), Darg et al (2010) for negative evidence, and Alonso et al (2007), Woods & Geller (2007), Rogers et al (2009), Koss (2010, and Ellison (2011) for an enhanced fraction of close pairs of AGN hosts compared to control samples -can hardly provide a definite clue to the minor merging/fly-by scenario (also because of the dependence of the results on the clustering scale). A support for the interactionbased picture can be found in the bluer colours of galaxies close to AGN hosts (see Shirasaki et al 2011;Kollatschny et al 2012), and in the observations of specific individual cases (see, e.g., Gonzalez Delgado et al 2002;Anderson et al 2013 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Major interactions have been proposed as a mechanism to trigger AGN activity in some cases (see review by Combes 2003;Ellison et al 2011;Liu et al 2012), although no clear relation was found in some studies using the SDSS (Li et al 2006(Li et al , 2008. Seyferts do not require external interactions to be fueled (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Basilakos & Plionis 2006). Supporting evidence that AGNs closely trace the distribution of galaxies was recently presented by Li et al (2006) based on an optically selected sample of narrow-line AGNs from the Sloan Digital Sky Survey.…”
Section: Introductionmentioning
confidence: 93%